Existence of the low price-earnings anomaly on the Stock Exchange of Singapore - Bik, Emerald Kiang Kiang (2008)
This study seeks to investigate the existence and significance of the low P/E effect in the context of the Stock Exchange of Singapore (SES). The low P/E anomaly has received much attention and interest since Basu (1977), which provided substantial evidence of such an anomaly. This amounted to a contradiction of the efficient market hypothesis (EMH). Further studies by several other researchers have also enhanced the understanding and extended the knowledge of the low P/E effect.